(untitled) (Fiep Bulletin - online, 2011)
This article retakes the history of the childhoods in Brazil, with the intention of giving support in process to two researches, which look goes to understand the universe that composes reception institutions goes children and adolescents, in two cities in the south of Rio Grande do Sul. The objective of this article will be of undoing adds ideas that they plows given the natural in our society, but that, however, they plows built culturally. They plows made descriptions of the they plows growing the researches in relation to the these children. It researches of qualitative stamp, but with forms of dates collections and of different analysis. The research Corpo e gênero: um acolhimento institucional na cidade do Rio grande - RS have the theme the perception of the construction/constitution of bodies and children’s gender sheltered in an institutional reception. The dates collection will be accomplished interviews through with the educators and employees that have direct contact with the children belonging to the shelters and through the field work registered in the diary form. And the research ""A Universidade vai à Casa Lar": olhares de crianças participantes de um projeto de extensão glances aim attn to understand the meaning of the extension project in subject, goes the participant children. This will look goes, through participant observation, of registration in field diary and of drawings with the children to understand the subject proposed by the research. They plows researches that approach different themes, however it looks goes, equally, to understand an universe little researched in our area, the physical education, that it plows the reception institutions goes children and adolescents. We intended to qualify and to contribute the discussions and the debates concerning the children and of the adolescents that there plows, looking attn these subjects the beings of rights and in it lives him the abandoned childhoods.